2009
DOI: 10.1016/j.molcel.2009.05.011
|View full text |Cite
|
Sign up to set email alerts
|

H3K4me3 Stimulates the V(D)J RAG Complex for Both Nicking and Hairpinning in trans in Addition to Tethering in cis: Implications for Translocations

Abstract: SUMMARY The PHD finger of the RAG2 polypeptide of the RAG1/RAG2 complex binds to the histone H3 modification, trimethylated lysine 4 (H3K4me3), and in some manner increases V(D)J recombination. However, in the absence of biochemical studies of H3K4me3 on purified RAG enzyme activity, the precise role of H3K4me3 has not been clear. Here, we find that H3K4me3 stimulates purified RAG enzymatic activity at both the nicking (2 to 5-fold) and hairpinning (3 to 11-fold) steps of V(D)J recombination. Remarkably, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
112
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 52 publications
7
112
1
Order By: Relevance
“…Shimazaki et al have shown that DNA hairpin formation by the RAG1 and RAG2 core proteins was stimulated by a trimethylated Histone H3 peptide (H3K4me3) and unaffected by the nonmodified peptide (13). We asked whether this stimulation could overcome the R2Ct-dependent inhibition of hairpin formation and complex formation characterized in our experiments.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Shimazaki et al have shown that DNA hairpin formation by the RAG1 and RAG2 core proteins was stimulated by a trimethylated Histone H3 peptide (H3K4me3) and unaffected by the nonmodified peptide (13). We asked whether this stimulation could overcome the R2Ct-dependent inhibition of hairpin formation and complex formation characterized in our experiments.…”
Section: Resultsmentioning
confidence: 85%
“…Correspondingly, cell-wide depletion of K4 methylation causes a decrease in recombination (10,11). Direct binding of the RAG2 plant homeodomain (PHD domain) to H3K4me3 peptides has been demonstrated both in solution and in a crystal structure (10,12), providing a plausible explanation of the role of H3K4 trimethylation by tethering of the RAG complex to the activated loci (13). Colocalization of RAG1/2 to H3K4me3 at antigen receptor loci was recently demonstrated in vivo (14).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Chromatin accessibility at gene segments has been studied extensively as a determinant of the tissue-and stagespecific mechanisms controlling V(D)J recombination (6,7). Germ-line transcription of gene segments leads to the deposition of H3K4me3, a histone modification that is recognized by RAG2 and augments endonuclease function of the RAG complex (8,9,45). As such, levels of chromatin accessibility and transcription at each Vβ segment may help determine its use in the preselection Tcrb repertoire.…”
Section: Role Of Chromatin Environment In Determining Vβ Recombinationmentioning
confidence: 99%
“…Apart from cis-elements in the immune receptor loci, including recombination signal sequence, enhancers and promoters [48,65], some trans-elements have been shown to play an important part in the regulation of V(D)J recombination [66][67][68]. Moreover, accumulating evidence has demonstrated the role of epigenetic factors in the regulation of V(D)J recombination, probably by altering the chromatin accessibility at the immune receptor loci [66,[69][70][71][72][73][74][75]. Future investigations into the upstream signals that regulate those known downstream regulators of V(D)J recombination should be able to provide insights into how the V(D)J recombination process can be manipulated.…”
Section: Future Challengesmentioning
confidence: 99%